The Influence of Profitability, Solvency, and Auditor’s Opinion to Audit Report Lag at Coal Mining Companies - Adlina Nindra Hapsari; Negina Kencono Putri; Triani Arofah (Bina Nusantara University, 2016)
Submitting financial statements adapted in accordance with accounting standards audited by a registered public accountant with Financial Service Authority known as Otoritas Jasa Keuangan (OJK) is required for every public company. In delivering financial reports to the public, there would be a delay affected by a period of audit reporting (audit report lag). The goal of this research was to determine the impact of profitability, solvency, and auditor’s opinion to audit report lag on sub-sector coal mining companies listed on the Indonesian Stock Exchange. Quantitative study with purposive sampling method was used as the research method. In addition, the data were obtained from the company’s financial statements which have been published. Multiple linear regression and hypothesis testing using t and f statistics with a confidence level of 5% were applied as the analysis technique. The amount of the research objects was 18 out of 22 classified companies from the period of 2012 to 2014. From this study, it can be concluded that both profitability and auditor’s opinion have significant influence on audit report lag. In contrast, solvency has no significant influence on audit report lag.